Odrezovanje mehkih materialov z velikimi hitrostmi - Pušavec, Franci (Strojniški vestnik, 2006)
Commonly used materials like soft grey cast iron represent a serious load for cutting-tool materials during dry high-speed cutting (HSC) due to the material's unique combination of properties, such as high toughness, ductility, hard inclusions and chemical wear resistance. Although these properties are desirable design requirements, they pose a great challenge to machining due to the high temperatures and stresses generated during the cutting to ensure high surface quality, process capability and productivity. This loading reduces the bonding strength of the tool substrate, thereby accelerating the tool wear. This paper provides guidelines for increasing soft grey cast iron's machinability during HSC. The improved machinability of such grey cast iron during HSC can be achieved by combining the appropriate tool material and machining technology adjusted to the part requirements defined by a customer.
Keywords: orodja; odrezavanje; siva litina; obraba